SEGMENT PERFORMANCE REPORT SEBAGAI ALAT PENILAIAN PRESTASI MANAJER PUSAT BIAYA (STUDI KASUS PADA UD. GADING JAYA) - Tenau, Korina; Morasa, Jenny; Pusung, Rudy J. (Universitas Sam Ratulangi, 2018)
In the company, needs to implement the division of tasks of each section. In order to determine the extent to which the management of each part has been carrying out the duties and responsibilities of each, hence the need for a method of performance appraisal is segment manager report performance. Segment Performance Report contains information about the grouping of certain costs in accordance with the concept . Purpose o the study was determine whether performance .The research was conducted in UD. Gading Jaya is located at Jl. Kairagi I Manado. Results of this study declare that a performance appraisal manager at UD. Gading Jaya still conventional because it still refers to the production cost report and the statement of income generated by the production department without seeing the direct of income generated by the production department without seeing the direct contribution of the section and according to conventional report.Keywords: Segment Performance Report, Assessment Manager